2004
DOI: 10.1063/1.1644623
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Si self-diffusion in SiO2: Effect of the Si/SiO2 interface including time-dependent diffusivity

Abstract: Structural relaxation and self-diffusion in covalent amorphous solids: Silicon nitride as a model system

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
71
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 17 publications
8
71
1
Order By: Relevance
“…In Si-rich silica Uematsu 14 has shown that SiO is the main diffusing species; this may be the limiting process in pressure relief for our case. The diffusivities obtained in the present work, which vary from 10 -20 cm 2 /s to 10 -23 cm 2 /s for our range of temperatures, are considerably larger than those reported in previous studies of diffusion under equilibrium or near-equilibrium conditions.…”
mentioning
confidence: 60%
“…In Si-rich silica Uematsu 14 has shown that SiO is the main diffusing species; this may be the limiting process in pressure relief for our case. The diffusivities obtained in the present work, which vary from 10 -20 cm 2 /s to 10 -23 cm 2 /s for our range of temperatures, are considerably larger than those reported in previous studies of diffusion under equilibrium or near-equilibrium conditions.…”
mentioning
confidence: 60%
“…It should be noted that KMC simulations with measured Si self-diffusivities [14,15] lead to too long annealing times or too high temperatures. Obviously, the diffusive Si mass transport by a mobile SiO 2 defect with local Si excess (that could either be named Si interstitial, SiO molecule [14], or oxygen vacancy [16]) does not necessarily follow the same mechanism than as the 28 SiO 2 / 30 SiO 2 interface broadening, which was analyzed in self-diffusivity studies. In this letter, the discrepancy between diffusive Si mass transport and Si self-diffusivity will not be discussed as our theoretical predictions aim at the reaction pathway of SiO x decomposition rather than at a quantitative prediction of annealing time and temperature.…”
mentioning
confidence: 99%
“…However, it is reported that in pillar oxidation, the total amount of Si is not preserved ("missing Si"). 4) Essentially, in the thermal oxidation of Si, some experimental 5,6) and theoretical studies [7][8][9][10] show that the self-diffusion of Si in SiO 2 is affected by SiO generated from the Si=SiO 2 interface. It is believed that the behavior of SiO is significantly related to three-dimensional oxidation.…”
Section: Introductionmentioning
confidence: 99%